Defensive Nymphs of the Woolly Aphid Thoracaphis kashifolia (Hemiptera) on the Oak Quercus glauca. (5th October 2016) - Kurosu, Utako; Aoki, Shigeyuki; Uematsu, Keigo; Kutsukake, Mayako; Fukatsu, Takema
Abstract : Aphid nymphs with enlarged fore- and mid-legs were found from woolly colonies of Thoracaphis kashifolia (Hormaphidinae, Nipponaphidini) on leaves of the evergreen Quercus glauca in Japan. It was shown that they grasped an introduced moth larva with their legs and some inserted their stylets deep into the body. These defenders were first-instar nymphs of the alate generation and were produced by aleyrodiform apterae from early September onward. There was a large variation in the size of their forelegs. First-instar nymphs (to be alates) produced early in the season had fore-femorotrochanters shorter than those produced later. The molting rate (the percentage of pharate individuals) of the latter was very low (less than 5% to zero), suggesting their semisterility. Although first-instar nymphs with various lengths of forelegs joined to attack moth larvae, these facts indicate that an incipient caste differentiation occurs within the first-instar nymphs of the alate generation.